TAFSIR BIL MA’TSUR DAN NARASI MUKJIZAT NABI MUSA: ANALISIS PENAFSIRAN AT-THABARI SURAH THAHA AYAT 20 - Khairun Nada; Akhmad Dasuki (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Tafsir At-Thabari is one of the classic interpretations that uses the method of bilma'tsur method, which is an approach based on the history of the Prophet, companions,and tabi'in. This method was developed in the 2nd century H and pioneered byfigures such as At-Thabari, who made his tafsir the main source of understanding the Qur'an through the Islamic tradition.in understanding the Qur'an through a strong Islamic tradition. The bilma'tsur approach provides a broad perspective in explaining the meaning of the Qur'anic verses,including in the story of the miracle of Prophet Moses in Surah Thaha verse 20. At-Thabari collects and analyzes these narrations, although there arepossibility of the inclusion of elements of Israiliyyat that need to be studied further. RelevanceAt-Thabari's tafsir in modern tafsir studies remains high, especially in thebil ma'tsur approach. Tafsir At-Thabari can be combined with the approach ofapproach that is based on rationality and historical-contextual approach.historical-contextual approach, as well as further studies on the role of Israiliyyat in classical tafsir.in classical tafsir. Thus, At-Thabari's tafsir is not only relevantin the traditional context, but also contributes to the broader study of modern Islam.modern Islamic studies.